PEMANFAATAN MANGROVE RHIZOPHORA APICULATA SEBAGAI PRODUK EKONOMI KOPI MANGROVE DALAM UPAYA PENINGKATAN EKONOMI MASYARAKAT DUSUN CEMARE DESA LEMBAR SELATAN - Astri, Ratih Nur; Ramadhan, Faras; Ummatin, Aulya Khaera; Fathurrahman, Fathurrahman (Universitas Mataram, 2024)
South Lembar Village is one of the villages located in Lembar District, West Lombok Regency. The area of this area is 433.35m2, which consists of eleven hamlets. One of the hamlets in South Lembar Village, namely Cemare Hamlet, is endowed with an abundance of natural resources in the form of Rhizophora Apiculata mangroves which in the use of natural resources have not been optimal. Community Kuliah Kerja Nyata Pemberdayaan Masyarakat Desa (KKN PMD) University of Mataram 2024 together with the Cemare Ecogreen Community has built a collaboration that aims to develop the economic potential of available natural resources in the form of processed mangrove fruit into Mangrove Coffee. The method used in this activity involves two main stages, namely (1) the process of making Mangrove Coffee and (2) marketing of Mangrove Coffee products. The process of making Mangrove Coffee starts from the process of picking, separation, cutting, soaking, drying, roasting, grinding, to the mixing process between mangrove fruit powder and local coffee. Meanwhile, Mangrove Coffee marketing starts from the process of sticker design, sticker printing, and product packaging. The results of this activity show that Mangrove Coffee products have the potential to improve the economy of the local community, and to encourage awareness of the importance of environmental conservation, mangrove seeding is carried out to become mangrove seedlings in the future.